Higher educational institutions students attitude to physical culture and sport - Радченко, О.; Хомич, А. (Slobozhanskyi Herald of Science and Sport, 2011)
The article deals with the attitude of female students to physical education classes in higher educational establishment. We analyzed the level of interest of the students of three Volyn universities to physical culture and sports, the motives of exercise. We study the interest of students towards which sports they like to do in sections in their free time. The state of systematic character of employments is also studied by a physical culture by students.